2002
DOI: 10.2355/isijinternational.42.80
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg and Si on the Microstructure and Corrosion Behavior of Zn-Al Hot Dip Coatings on Low Carbon Steel.

Abstract: Fig. 11. Magnified SEM photographs of the cross-sections of the inner, alloy layer in (a) the Zn-6Al coat and (b) the Zn6Al-0.5Mg-0.1Si coated film after corrosion in a 5 % NaCl solution at room temperature for 1.8 ks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
1
4
0
8
Order By: Relevance
“…The solid solution phases (Al) and (Si) and the intermetallics Mg 2 Si and MgZn 2 are able to improve the wear resistance of Al-Zn based alloy and the corrosion resistance of the hot-dip Al-Zn alloy coating. In the work of Tanaka et al [5], Mg and Si in the outer adhered layer and Si in the inner alloy layer make the Zn-6Al-0.5Mg-0.1Si (in weight pct) coating more anti-corrosive. Morimoto et al [6] found that the increase of Al, Mg contents in coating and the addition of Si improved corrosion resistance of the coating in salt spray tests.…”
Section: Introductionmentioning
confidence: 97%
“…The solid solution phases (Al) and (Si) and the intermetallics Mg 2 Si and MgZn 2 are able to improve the wear resistance of Al-Zn based alloy and the corrosion resistance of the hot-dip Al-Zn alloy coating. In the work of Tanaka et al [5], Mg and Si in the outer adhered layer and Si in the inner alloy layer make the Zn-6Al-0.5Mg-0.1Si (in weight pct) coating more anti-corrosive. Morimoto et al [6] found that the increase of Al, Mg contents in coating and the addition of Si improved corrosion resistance of the coating in salt spray tests.…”
Section: Introductionmentioning
confidence: 97%
“…However, small additions of Mg in Zn alloys (up to 12%) can reduce the corrosion rate of Zn alloy, especially in the case of atmospheric corrosion (e.g., building application). For instance, Tanaka et al [23] added Mg to the Zn-Al alloy bath and investigated the behavior of the Zn-6 wt % Al-Mg coating, and their results show a beneficial effect of Mg in prevention of corrosion. In the study of Zhu [24], the neutral salt spray and electrochemical test are performed to evaluate the corrosive resistance of the 23Al-Zn-0.3Si (wt %) coating, and the results show that Mg can improve the corrosive resistance and the formability of 23Al-Zn-0.3Si (wt %) coating.…”
Section: Introductionmentioning
confidence: 99%
“…Además de que la cantidad de aluminio que entra en la capa del recubrimiento representa un problema adicional en la composición del baño, ya que se reduce considerablemente la concentración de aluminio, lo que genera un continuo monitoreo [4]. En este sentido, Tanaka et al [12] evaluaron recubrimientos sobre acero con bajo contenido de carbono por inmersión en caliente en dos etapas (doble inmersión), principalmente en un baño de Zn y luego en un baño de Zn-6Al (Z6A) con o sin adición de 0,5 % en peso de Mg y 0,1 % en peso de Si (Z6AMS). En la Figura 6 se muestra la morfología de la superficie de los recubrimientos formados por la inmersión en caliente de dos etapas con baños secundarios de Z6A (a) y Z6AMS (b).…”
Section: Desarrollo De Recubrimientos De Zinc Sobre Acerounclassified
“…Así se tiene, que el desarrollo de los recubrimientos de zinc por inmersión en caliente se ha basado en modificar la composición química del baño, lo cual implica cambios microestructurales que mejoran sus propiedades para una aplicación específica. Los elementos de aleación que más se han estudiado con el fin de establecer su influencia en las propiedades generales de estos recubrimientos son el aluminio [3,6,[13][14][15][16][17], el magnesio [2,[10][11][12][16][17][18][19]] y el silicio [2]. Otros elementos que en menor proporción se han estudiado son el cobre [1,20], el titanio, el níquel [21,22], etc.…”
Section: Desarrollo De Recubrimientos De Zinc Sobre Acerounclassified
See 1 more Smart Citation